Дисфункція нюху при COVID-19: особливості перебігу у гострому та постковідному періоді - Кравченко, Ірина Михайлівна; Морозова, Ольга Григорівна; Ярошевський, Олександр Анатолійович; Реміняк, Інна Вадимівна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Пандемія коронавірусної хвороби (COVID-19) викликана новим коронавірусом є глобальною проблемою з точки зору навантаження на системи охорони здоров’я й робить вагомий внесок в напрямки наукових досліджень в різних сферах. Мета. Аналіз типового симптомокомплексу гострого COVID-19 у пацієнтів із тривалою аносмією в системному взаємозв’язку з психосоматичними та неврологічними проявами впродовж 9 міс динамічного спостереження після завершення епізоду та встановлення напрямків підвищення ефективності лікувально-профілактичної допомоги. Матеріали та методи. Програма обстеження складалася з двох фрагментів. Перший – включав вивчення та аналіз соматичного, неврологічного та психічного статусу пацієнтів із аносмією в період гострої фази COVID-19, другий – динамічне спостереження впродовж дев’яти міс після перенесеного захворювання з проведенням ретроспективного аналізу основних симптомів та синдромів. Отримані результати. Встановлено клінічний поліморфізм нейровегетативних проявів гострого епізоду захворювання та перебігу постковідного періоду. Проведено дослідження системних взаємозв’язків виявлених типових нейровегетативних, психоневрологічних та соматичних проявів, встановлено найбільш значущі детермінанти розвитку тривожних і депресивних станів у пацієнтів в постковідному періоді та обґрунтовано актуальність напрямків подальших досліджень. Висновки. Тривала (більше 4 тиж) аносмія є предиктором формування тривожно-депресивних станів і впливає на розвиток порушень сну у пацієнтів із групи спостереження.

Introduction. The pandemic of coronavirus disease (COVID-19) caused by the novel coronavirus is a global problem in terms of the burden on health care systems and makes a significant contribution to the areas of scientific research in various fields. The high socio-economic and medical significance of COVID-19 requires the search for sound scientific information about it in terms of clinical and pathophysiological heterogeneity of the disease. Purpose of the study. To analyze the typical symptom complex of acute COVID-19 in patients with prolonged anosmia in a systemic relationship with psychosomatic and neurological manifestations during 9 months of dynamic follow-up after the episode and to identify ways to improve the effectiveness of treatment and prevention care. Materials and methods. The examination program consisted of two parts. The first one included the study and analysis of the somatic, neurological and mental status of patients with anosmia during the acute phase of COVID-19, the second one - dynamic follow-up for nine months after the disease with a retrospective analysis of the main symptoms and syndromes. The results. According to a systematic analysis of 154 completed cases of COVID-19 in patients who received medical care exclusively on an outpatient basis, clinical polymorphism of neurovegetative manifestations of the acute episode of the disease and the course of the post-COVID period was established. The systemic interrelationships of the identified typical neurovegetative, neuropsychiatric and somatic manifestations were studied, the most significant determinants of the development of anxiety and depression in patients in the post-COVID period were identified, and the relevance of further research was substantiated. Conclusions. Prolonged (more than 4 weeks) anosmia is a predictor of the formation of anxiety and depression and affects the development of sleep disorders in patients from the observation group.
Olfactory dysfunction in COVID-19: features of the course in the acute and post-COVID period
Keywords: COVID-19; гострий епізод; аносмія; дисгевзія; постковідний синдром; депресія; тривога; когнітивний дефіцит; нейровегетативні прояви; acute episode; anosmia; dysgeusia; post-COVID syndrome; depression; anxiety; cognitive deficit; neurovegetative manifestations